Converting corncob waste into liquid smoke and biochar: A circular energy initiative in Naramben Village - Rolling Gasperzs; Marthina Mini; Helen Riupassa; Susi Marianingsih; Suyatno Suyatno; Hendry Y. Nanlohy (Community Empowerment, 2026)
Corncob waste in Naramben Village is traditionally underutilized and frequently subjected to open burning, leading to air pollution and localized environmental degradation. This program introduces simple pyrolysis technology to equip local residents with the practical skills needed to transform this agricultural waste into value-added commodities: liquid smoke and biochar. Executed through a participatory framework, the initiative combined strategic preparation, hands-on production workshops, and educational dissemination. The program drove a substantial shift in community renewable energy literacy, with participants successfully adopting liquid smoke as an organic pesticide and natural fish preservative. From a technical standpoint, utilizing a 50-liter drum-type pyrolyzer over a two-hour cycle consistently yielded 1.5 to 2 liters of liquid smoke and 5 kg of biochar per batch. Evaluations confirmed that the direct demonstration approach effectively fostered operational independence among the villagers. Ultimately, this localized waste-to-energy model mitigates open-burning pollution, unlocks new micro-economic avenues, and advances clean energy resilience.